Study Healthy Ageing Lansia pada Masa Pandemi COVID-19 di Kelurahan Sukarame Bandar Lampung Ditinjau dari Kedokteran - Shyffa Khairunnisa S. Raya; Harliansyah Harliansyah; Kuslestari Kuslestari (Publikasi Indonesia, 2022)
COVID-19 is a widespread global health problem with a rapid and easy way of transmission. With a high death rate, the government implements a lock down that indirectly reduces the space for people to move. This then relate to the health and productivity of the elderly in achieving healthy aging in the elderly. : This study aims to see if there is a healthy aging movement carried out by the elderly in Sukarame Village, Bandar Lampung during the COVID-19 pandemic. The method in this research is qualitative phenomenology. The study was conducted through interviews with respondents with criteria for healthy and active elderly in Sukarame Village, Bandar Lampung. Samples were determined by means of Purposive Sampling. The data were analyzed using three stages, namely data reduction, data presentation, and drawing conclusions using correlation test bivariate Spearman's Rho. In the study, it was found that 87% of respondents were still physically active. As many as 97% of respondents have a good and sufficient appetite. It was found that 75% of the respondents were non-smokers. Of the total respondents, there are 20% of respondents who are still working. All respondents are still involved in environmental and social activities. All the healthy aging carried out by the respondents are very strongly and strongly related to each other. The mood of the elderly has a significant impact on the satisfaction that the elderly feel. The healthy aging movement was found in respondents in Sukarame Village, Bandar Lampung.